EXPLORING THE IMPACT OF REGULATORY MEASURES ON CAPITAL AND RISK-TAKING OF TUNISIAN BANKS - Louzis, D. P; Vouldis, A. T (Economics and Statistics Research Journal (ESRJ), 2022)
This study examines the long-term determinants of capital buffers and risk-taking adjustments of listed Tunisian commercial banks in response to regulatory and macroeconomic events in the post-revolution era. The research uses a panel autoregressive distributed lags technique to investigate the factors that influence the capital and risk-taking decisions in Tunisian banks, taking into account the impact of bank-specific, macroeconomic and regulatory variables. The empirical findings suggest that capital standards are still a significant prudential tool for maintaining the robustness of Tunisian banks. However, the study also confirms the existence of a moral hazard and procyclical behavior of Tunisian banks in response to capital requirements. Moreover, the sample size could be extended if more data were available, and a possible long-term simultaneous relationship between capital and risk-taking was not considered. The study recommends that Tunisian banks diversify their sources of revenue and revise their business models to become less dependent on revenue from traditional intermediation activities. By doing so, they will be able to reduce the procyclicality of the banking system and minimize the banking risks.